2010
DOI: 10.1007/s00198-010-1391-2
|View full text |Cite
|
Sign up to set email alerts
|

Does timing of surgery matter in fragility hip fractures?

Abstract: The effect of delay of surgery on the geriatric hip fractures has been a subject of interest in the past two decades. While the elderly patients will not tolerate long periods of immobilization, it is still unclear how soon these surgeries need to be performed. A review of existing literature was performed to examine the effect of timing of surgery on the different outcome parameters of these patients. Although there is conflicting evidence that early surgery would improve mortality, there is widespread eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 43 publications
(58 reference statements)
2
60
0
1
Order By: Relevance
“…Therefore, the study findings gave a review without taking special clinical situations into consideration. In general, intertrochanteric fracture treatment includes patients with advanced age, and other factors such as social dependence, cachexia, anemia, cognitive dysfunction, and additional comorbidities lead to a high mortality rate [7,19,29,32,42]. Despite the potential for bias, our data suggest the AO/ OTA classification is widely used in Germany (65%-88% of hospitals) and other instability criteria (lateral wall breach, detached greater trochanter, comminution of the posteromedial cortex) played a secondary role.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Therefore, the study findings gave a review without taking special clinical situations into consideration. In general, intertrochanteric fracture treatment includes patients with advanced age, and other factors such as social dependence, cachexia, anemia, cognitive dysfunction, and additional comorbidities lead to a high mortality rate [7,19,29,32,42]. Despite the potential for bias, our data suggest the AO/ OTA classification is widely used in Germany (65%-88% of hospitals) and other instability criteria (lateral wall breach, detached greater trochanter, comminution of the posteromedial cortex) played a secondary role.…”
Section: Resultsmentioning
confidence: 76%
“…Since the estimates in this survey were self-reported, this may be a topic for randomized clinical multicenter studies in the future. Another explanation could be the fact that there is a low clinical and radiographic followup rate regarding these fragile patients with many comorbidities [7,19,29,32,42]. Our survey suggested only 2% of respondents would always manage unstable intertrochanteric fractures with extramedullary plate systems, although a number of studies [3,18,21,35,38] have reported no difference in the reoperation rates after treatment with an intramedullary or extramedullary device.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations